A Study of the Pattern of Admissions to the Accident and Emergency (A&E) Department of a Tertiary Care Hospital in Sri Lanka. (13th August 2020) - Jayasekera, Priyamali; Dassanayake, Gayani; Bandara, Kasthuri; Jayawardhena, Lakmali; Malkanthi, K. M. S.
Abstract : Introduction . The latest national healthcare reform policies of Sri Lanka include the development of accident and emergency (A&E) departments in all major hospitals. Provincial General Hospital Kurunegala (PGHK) is a home to the first established A&E department in Sri Lanka. PGHK provides services to a population of 2.4 million spread out in the North Western Province and part of the Sabaragamuwa Province. This study was carried out to identify the pattern of all admissions to the A&E department of PGHK. Methods . The prospective observational study was carried out from July 1, 2016, to June 30, 2017 (one year) to identify the pattern of admissions to the A&E department. Results . There were 49, 213 admissions to PGHK's A&E department during the study period. The average number of admissions was 135 (±17.9) per day. The percentage of deaths in the A&E department was 0.21%. The mean age of admitted patients was 46.7 (±21.7) years. A further 62% of admitted patients were males. The number of medical, surgical, paediatric, and gynaecological and obstetrical admissions was 55%, 42%, 3.5%, and 0.22%, respectively. Among the common emergency medical presentations, 34% were chest pain, 11% patients presented with unilateral weakness and/or slurring of speech, 10% covered dyspnoea, and 9% complained of dizziness/giddiness. Among emergency surgical presentations, 83% were trauma due to accidents, of which 27% were road-traffic-related accidents (RTAs). Discussion . The A&E department of PGHK provides services to a significantly high number of health emergencies every day. The majority of these admissions was due to chest pain and trauma related to accidents. The lower recorded number of paediatric and gynaecological and obstetrical emergencies presented to the A&E department is a result of a government policy mandating the admission of these types of patients directly to their respective wards. Further infrastructure development, staff recruitment, and training have to be planned and implemented to address the significantly high number of admissions to the A&E Department of PGHK.